Nixon, Ford, Kissinger, and the Holy Crown of Hungary in Bilateral Relations - Glant, Tibor (Hungarian Journal of English and American Studies, 2021)
The Holy Crown of Hungary spent thirty-three years in American custody between the end of World War II and its repatriation in January 1978. Open hostility between the US, the leader of the Free World, and Hungary, a Soviet colony in the middle of Europe, prevented any discussion about its return between 1947 and 1970. The normalization of bilateral relations (1969-78) opened up new possibilities, and the Nixon White House considered the return of the Hungarian coronation regalia briefly in 1970-71. Spirited protests by Congressmen and East European immigrants convinced National Security Adviser Henry Kissinger and President Nixon that they could lose more by returning the Crown than by keeping it in American custody (in Fort Knox, KY), so the issue was dropped. Yet the press continued to discuss the possibility of its return and the White House had to deny any such plans again and again. As normalization ground to a halt after 1973, Budapest exerted more and more pressure and the matter was on President Ford’s desk one last time in December 1976, right after he had lost the election. Ford accepted the advice of his foreign policy team and “sleeping dogs” were left alone. It was the next president who decided to “face the goulash hitting the fan” and the Holy Crown of Hungary and the assorted regalia were returned by the new Carter administration on January 6, 1978. (TG)